ANALISIS PENGELOLAAN SUMBER DAYA MANUSIA PADA LEMBAGA PENDIDIKAN MENYONGSONG IMPLEMENTASI KURIKULUM MERDEKA - Muchlip M, Cipnal (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
Management of human resources is absolutely necessary in an institution or organization. Unfortunately, management practices in educational institutions have not been carried out properly and systematically. This study aims to analyze the practice of managing human resources in schools, especially in relation to the implementation of the independent curriculum. The research method used in this research is descriptive qualitative. Data obtained through interviews and observation. Interviews were conducted with teachers, principals and vice curricula. The results of the study show that (1) most schools do not have a special department in charge of managing human resources. (2) Schools enthusiastically welcome the implementation of the independent curriculum, although they feel that there are still many things they don’t know and need to know (3) The independent curriculum requires teachers to have independence, self-integrity. An independent curriculum decmands that every teacher has learning and teaching independence, for this reason it is necessary to manage teaching and educational staff so that they are in harmony with the challenges of Kurikulum Merdeka.